A secure model for prevention of black hole attack in wireless mobile ad hoc networks - Araghi, Tanya Koohpayeh (2013)
Implementing Ad hoc networks are becoming very prevalent during recent years. Security is the most important issue for developing mobile ad hoc networks (MANETs). They expose to various kinds of attacks because of their unique nature in which every node can easily join to network or leave it. Black hole attack is the most probable attack in MANET. In this research we proposed a model for prevention of this attack. It judges on route replies coming from the intermediate node based on a trusted third party which is the destination node. If the source node received an acknowledgement on the route replies sending by an intermediate node, from destination during a specific time, it decides that the path is safe and intermediate node is not malicious. Meanwhile a counter will be set for counting the number of times that each intermediate node introduced a wrong route reply. Every node that proposes a wrong route reply will be recorded in a black list. The process also will be checked for all one hop neighbors of the suspicious node and the history of these nodes will be gathered in the black list, if they proposed a wrong route reply during the route discovery process. When the counter for each node exceed from a specific value, the chain of suspicious nodes will be introduced as black holes and an alarm will be notified to all nodes in the network to remove these malicious nodes from their routing tables.